(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
This article explores the concept of anthropomorphism and its pervasive role in modern communication, highlighting its impact across various fields such as advertising, technology, media, and entertainment. Anthropomorphism, the attribution of human characteristics to non-human entities, facilitates emotional engagement, relatability, and stronger connections between users and products, characters, or systems. The article concludes that anthropomorphism continues to shape how we interact with both the digital and physical world, offering a bridge between human experience and non-human entities. It emphasizes the growing significance of anthropomorphism as technology evolves, offering a more personalized, empathetic, and engaging communication experience in our increasingly digital and mediated lives.